Mobile methods - Buscher, Monika; Urry, John; Witchger, Katian (London Routledge, 2011)
In the twenty-first century, more than ever, everything and everybody seems to be on the move. Global flows of people, goods, food, money, information, services and media images are forming an intensely mobile background to everyday life. Social scientists, too, are on the move, seeking new analytical purchase on these important aspects of the social world by trying to move with, and to be moved by, the fleeting, distributed, multiple, non-causal, sensory, emotional and kinaesthetic.